Assessing the so called Marked Inflectional Features of the Nigerian English: a Second Language Acquisition Theory Account - Oshodi, Boluwaji (Íkala, Revista de Lenguaje y Cultura, 2014)
There are conflicting claims among scholars on whether the structural outputs of the types of English spoken in countries where English is used as a second language gives such speech forms the status of varieties of English. This study examined those morphological features considered to be marked features of the variety spoken in Nigeria according to Kirkpatrick (2011) and the variety spoken in Malaysia by considering the claims of the Missing Surface Inflection Hypothesis (MSIH) a Second Language Acquisition theory which accounts for the cause of the variable use of such inflections among L2 learners. Results from oral and written composition tasks administered on selected undergraduate students of Nigerian and Malaysian universities revealed that what is regarded as morphological features are actually a deviation from the L2 target forms. According to the MSIH the variability in the use of such inflections is due to problems of lexical retrieval a psycholinguistic problem which manifests among L2 learners of English generally which results in wrong surface representations.